Beneng Taro Starch and Chitosan Effect on Edible Film Characteristics - Merynda Indriyani Syafutri; Monica Satya Widyatantri; Budi Santoso; Onne Akbar Nur Ichsan; Nura Malahayati; Desi Aryani; Trubus Airlangga (University of Sultan Ageng Tirtayasa, 2026)
Packaging materials made of plastic have caused quite serious problems. Taro beneng tubers have the potential as an ingredient in making edible films because of starch content. The quality of edible film is influenced by the concentration of starch and chitosan as constituent components in the manufacture of edible film. This study aimed to determine the effect of different concentrations of beneng taro starch and chitosan on the physicochemical characteristics of edible film. This study used a Factorial Complete Randomized Design with two treatment factors: concentration of beneng taro starch (7%, 8%, and 9%) and concentration of chitosan (0.5%, 1%, and 1.5%). The results showed that concentration of beneng taro starch had significant effect on the percent value of elongation (%), thickness (mm), compressive strength (gf), white degree (%), and water vapour transmission rate (g.m-2.day-1), while chitosan concentration had a considerable effect on the percent value of elongation, thickness, compressive strength, white degree, and water vapour transmission rate of edible film. The best treatment was edible film with concentration of beneng taro starch 7% and chitosan concentration 0.5% with 24.00% of elongation, 0.21 mm of thickness, 80.77 gf of compressive strength, 75.05% of white degree, and 41.49 g.m-2.day-1 of water vapour transmission rate.